Monthly environmental and greenhouse gas data in green-tide hotspots on Jeju Island, KoreaZenodo - Seo-Young Kim; Hyo-Ryeon Kim; Jae-Hyun Lim; Ju-Hyoung Kim; Il-Nam Kim (Data in Brief)
The coastal waters of Jeju Island, Korea, experience recurrent macroalgal blooms, particularly green tides, driven by nutrient enrichment and anthropogenic activities. The semi-enclosed bays of Jeju Island—Jocheon, Gimnyeong, and Sinyang—are especially vulnerable to eutrophication due to prolonged water residence times and accumulation of terrestrial pollutants. We provide a time-series dataset of monthly measurements of environmental parameters and greenhouse gas concentrations collected from March to November 2020 at 12 stations across the three bays. Surface seawater temperature, salinity, and dissolved oxygen were measured in situ using a calibrated portable multi-parameter probe. Additionally, discrete seawater samples were collected using a 10 L Niskin sampler for biogeochemical parameters (nutrients, pHT, total alkalinity) and greenhouse gas concentrations (CO2, CH4, and N2O). This dataset provides insights into the spatiotemporal dynamics of physical-biogeochemical properties and greenhouse gas concentrations associated with green tides, and serves as a valuable resource for understanding how coastal ecosystems respond to environmental changes.